Age‐related sensory neuropathy in patients with spinal muscular atrophy type 1 - Pro, Stefano; Tozzi, Alberto Eugenio; D'Amico, Adele; Catteruccia, Michela; Cherchi, Claudio; De Luca, Massimiliano; Nicita, Francesco; Diodato, Daria; Cutrera, Renato; Bertini, Enrico; Valeriani, Massimiliano (Muscle & nerve, 2021)
Introduction/Aims Spinal muscular atrophy type 1 (SMA 1) is a devastating motor neuron disorder that leads to progressive muscle weakness, respiratory failure and premature death. Although sensory electrophysiological changes have been anecdotally found in pediatric SMA 1 patients, the age of onset of sensory neuropathy remains unknown. Methods Sensory nerve conduction studies of the median and sural nerves were performed in 28 consecutive SMA 1 patients of different ages. Sensory nerve conduction velocities and sensory nerve action potential (SNAP) amplitudes recorded in these patients were compared with those obtained from 93 healthy subjects stratified by age. Results SNAP amplitudes decreased with increasing age in the sural and median nerves, without any significant difference between upper and lower limbs. Discussion Our data suggest that sural and median nerve SNAP amplitudes are normal in younger patients, while an axonal neuropathy appears in older ones.